Directional Dark Matter Searches with the CYGNO Project. (February 2020) - Baracchini, E; Bedogni, R; Bellini, F; Benussi, L; Bianco, S; Capoccia, C; Caponero, M; Cavoto, G; Costa, I A; Di Marco, E; D'Imperio, G; Iacoangeli, F; et al.
Abstract: The goal of the CYGNO project is to deploy at Laboratori Nazionali del Gran Sasso (LNGS) an high resolution Time Projection Chamber (TPC) with Gas Electron Multipliers (GEMs) amplification and optical 3D readout of an Helium/Fluorine based gas mixture for directional Dark Matter (DM) searches at low 1-10 GeV WIMP masses. The determination of the incoming direction of WIMP particles can in fact offer not only additional handles for discrimination of the annoying backgrounds, but especially an unique key for a positive, unambiguous identification of a DM signal.